Vasoprotective Endothelial Effects of Chronic Cannabidiol Treatment and Its Influence on the Endocannabinoid System in Rats with Primary and Secondary Hypertension - Marta Baranowska-Kuczko (MDPI AG, 2021)
Our study aimed to examine the endothelium (vascular)-protecting effects of chronic cannabidiol (CBD) administration (10 mg/kg once daily for 2 weeks) in aortas and small mesenteric (G3) arteries isolated from deoxycorticosterone-induced hypertensive (DOCA-salt) rats and spontaneously hypertensive rats (SHR). CBD reduced hypertrophy and improved the endothelium-dependent vasodilation in response to acetylcholine in the aortas and G3 of DOCA-salt rats and SHR. The enhancement of vasorelaxation was prevented by the inhibition of nitric oxide (NO) with L-NAME and/or the inhibition of cyclooxygenase (COX) with indomethacin in the aortas and G3 of DOCA-salt and SHR, respectively. The mechanism of the CBD-mediated improvement of endothelial function in hypertensive vessels depends on the vessel diameter and may be associated with its NO-, the intermediate-conductance calcium-activated potassium channel- or NO-, COX-, the intermediate and the small-conductance calcium-activated potassium channels-dependent effect in aortas and G3, respectively. CBD increased the vascular expression of the cannabinoid CB1 and CB2 receptors and aortic levels of endocannabinoids with vasorelaxant properties e.g., anandamide, 2-arachidonoylglycerol and palmitoyl ethanolamide in aortas of DOCA-salt and/or SHR. In conclusion, CBD treatment has vasoprotective effects in hypertensive rats, in a vessel-size- and hypertension-model-independent manner, at least partly via inducing local vascular changes in the endocannabinoid system.